Trace Metal Concentrations in marine species in the Bay of Huarmey, Ancash, Peru - Jacinto, María E. (2007)
Trace concentrations of cadmium, copper, lead and zinc were determinated in muscles and internal organs of rock shell (Stramonita T. chocolata), hairy rockcrab (Cancer setosus), Peruvian rock seabass (Paralabrax humeralis), small mussel (Semimytilus algosus), keyhole limpet (Fissurella spp.) and chiton (Chiton spp.) collected in October 2001 from Huarmey bay, Ancash, Peru. The selected organs were liophylized and process according to CEM the USA 1994 and analyzed by atomic absorption spectrophotometry. Lower concentrations of cadmium (0,63 μg/g), copper (1,87 μg/g) and zinc (1,70 μg/g) were observed in P. humeralis muscle, in contrast higher values of zinc (24,16 μg/g) was in T. chocolata and copper (28,0 μg/g) in muscle of Chiton spp. Trace concentrations were within the international standard limits established by some countries (Nauen, 1983).